Molecular characterization of free-living nematodes from Kermadec Trench (Nematoda: Aegialoalaimidae, Xyalidae) with description of Aegialoalaimus tereticauda n. sp. - Leduc, Daniel; Zhao, Zeng Qi (Zootaxa, 2021)
The Kermadec Trench is the world’s fifth deepest trench and extends from approximately 26 to 36°S near the northeastern tip of New Zealand’s North Island. Here, we describe a new species of Aegialoalaimus, a nematode genus with unusual buccal cavity and pharynx morphology, from a site at 9540 metres water depth in Kermadec Trench, and provide the first SSU and D2–D3 of LSU sequences for Aegialoalaimus, Manganonema, Metasphaerolaimus constrictus and Daptonema amphorum. Aegialoalaimus tereticauda n. sp. is characterised by body length 755–864 µm, cephalic sensilla papilliform (< 1 µm long), excretory pore located slightly anterior to posterior bulb in males and slightly anterior to nerve ring in females, arcuate spicules 18–22 µm long, gubernaculum present, precloacal supplements absent, and cylindrical tail 58–64 µm long with rounded tip. Relationships between Aegialoalaimus and Chromadorean orders could not be elucidated based on our SSU analysis; no link could be found with the Plectida, where the Aegialoalaimidae is currently placed, or with the Isolamiida or Cylindrolaimus (Areaolaimida), which share a similar and unusual buccal and pharynx morphology. Our SSU phylogenetic analysis confirms the placement of Manganonema within the Xyalidae, although relationships with other xyalid genera remain unclear. The Sphaerolaimidae formed a clade together with the Monhysteridae, which contradicts the current classification where the Sphaerolaimidae and Xyalidae are classified together into the superfamily Sphaerolaimoidea and the Monhysteridae into the Monhysteroidea. Although limited research has been conducted on the nematode diversity in Kermadec Trench to date, the available data show that half of all invertebrate species known from the trench are nematodes, which highlights the importance of conducting further taxonomic research on this group in hadal environments.